The Use of The Make A Match Method In Improving Learning Outcomes in Mathematics Learning at State Primary School 136541 Tanjungbalai City - Hutasuhut, Annisa Aulia; Basri, Muhammad; Zunidar, Zunidar (International Journal of Education, Information Technology, and Others, 2024)
The problems found in this research were: low student mathematics learning outcomes, feeling bored while studying, lack of interest and attention of students towards the teacher during learning. This research aims to determine the learning outcomes of students at SD Negeri 136541 Tanjungbalai City for the 2023/2024 academic year learning mathematics on fractions, decimal and whole numbers. In cycle I, meeting I, there were no students who got a very high category score (0%), 2 students (8%) got a high category score, 11 students (40%) got a low category score, and 13 students (52%) got a very low category value. In cycle I, meeting II, there were no students who got a score in the very high category (0%), 7 students (24%) in the high score category, 9 students (36%) in the low score category, and 10 students (40%) in the very score category. low. There was an increase in the completeness of student learning outcomes in cycle II. This can be seen in the data from cycle II of meeting I, as many as 5 students (20%) were in the very high score category, 11 students (40%) got a score in the high score category, 8 students (32%) were in the low score category, and 2 students (8%) fall into the very low score category. In cycle II, 20 students (76%) got a score in the very high category, 5 students (20%) were in the high score category, 1 student (4%) had a low score, and there were no students who were in the very low category ( 0%). For the teacher's ability in the learning process in cycles I and II, the results were 2.4 and 2.7 in the quite good category. Meanwhile, in cycle II, meetings I and II obtained scores of 3.6 and 3.8 in the very good category. So it can be concluded that using the Make A Match method can improve the learning outcomes of class V students at SD Negeri 136541 Tanjungbalai City for the 2023/2024 Academic Year. The Make A Match learning method can make students active in thinking when doing assignments and more enthusiastic in learning.